Development of a colloidal gold immunochromatographic strip with enhanced signal for the detection of bovine parvovirus - Yu, Xiaoli; Jiang, Yanping; Zhang, Songsong; Wang, Caihong; Wang, Ruichong; Zhang, Lanlan; Tao, Siming; Cui, Wen; Li, Jiaxuan; Qiao, Xinyuan (Frontiers in Microbiology, 2023)
Bovine parvovirus (BPV) is a pathogen responsible for respiratory and digestive tract symptoms in calves and abortion and stillbirth in pregnant cows. In this study, we developed a colloidal gold immunochromatographic (GICG) strip with an enhanced signal for detecting BPV according to the double-antibody sandwich principle and an enzyme-based signal amplification system to amplify the signal. This system utilizes horseradish peroxidase reacting with a substrate solution containing 3,3′,5,5′-tetramethylbenzidine and dextran sulfate to obtain insoluble blue products on the test and control lines. We optimized different reaction conditions, including the amount of monoclonal antibodies (mAbs), pH of the colloidal gold solution, coating solution, blocking solution, sample pad treatment solution, antibody concentration in the control line, and antibody concentration in the detection line. The sensitivity of the signal-enhanced GICG strip showed that the minimum amount for detecting BPV was 102 TCID50, 10 times higher than that of the traditional GICG strip. The results of the specificity test showed that the signal-enhanced GICG strip had no cross-reactivity with BRV, BVDV, or BRSV. The results of the repeatability test showed that the coefficient of variation between and within batches was less than 5%, showing good repeatability. Moreover, for validation, PCR and the signal-enhanced GICG strip were used to detect 280 clinical bovine fecal samples. The concordance rate compared with PCR was 99.29%. Hence, the developed strip exhibited high sensitivity and specificity for the detection of BPV. Therefore, this strip could be a rapid, convenient, and effective method for the diagnosis of BPV infection in the field.